PENERAPAN EMOTIONAL LABOR DALAM KONTEKS PEKERJA GENERASI Z: SEBUAH PENDEKATAN FENOMENOLOGIS - I Gusti Ayu Wirati Adriati; Victor Joshua Nugroho; I Putu Dharmawan Pradhana (LPSDI Bina Patria, 2025)
This study examines the implementation of Emotional Labor among Generation Z workers, focusing on the emotional challenges they face in the workplace, especially in coffee shops. Generation Z, an innovative but stress-prone generation, is often exposed to pressure from personal problems that can affect their performance. This study explores workers' experiences in managing emotions amid high work demands through a phenomenological approach. Data were obtained through interviews with employees and managers from various coffee shops and psychology practitioners. The study results indicate that the ability to control emotions and implement effective coping strategies is essential for Gen Z workers in maintaining work performance. In addition, support from management in creating a positive work environment and emotional skills training programs are needed to help them overcome existing challenges. These findings provide new insights into the importance of managing Emotional Labor in the workplace and implications for developing better human resource policies that can support employee mental health and performance in the modern era.